THEORY, DISCOURSE AND REALITY IN THE POLITICAL PROCESS - Швирков, О.І. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2012)
The paper presents a problem field generated by the attitudes between socio-political modernist theories, discourses generated by these theories and socio-political reality which is coincided as a set of social and political institutions. The attempt to determine the directions of further researches was made. The critical analysis of methodological base required for these studies was also made.